Optimization of Frequency Lowering Algorithms for Getting the Highest Speech Intelligibility Improvement by Hearing Loss Simulation. - Arıöz, Umut; Günel, Banu (Journal of Medical Systems, 2015)
High frequency hearing loss is a growing problem for both children and adults. To overcome this impairment, different frequency lowering methods (FLMs) were tried from 1930s, however no satisfaction was provided up to now. In this study, for getting higher speech intelligibility, eight combinations of FLMs which were designed originally were tried with simulated sounds onto normal hearing subjects. These improvements were calculated by the difference with standard hearing aid method, amplification. High frequency hearing loss was simulated with the combined suprathreshold effects. An offline study was carried out for each subject for determining the significant methods used in modified rhyme test (MRT) (Subjective measure for intelligibility). Significant methods were determined according to their speech intelligibility index (SII) (Objective measure for intelligibility). All different cases were tried under four noisy environments and a noise free environment. Twelve hearing impaired subjects were simulated by hearing loss simulation (HLS). MRT was developed for Turkish language as a first time. As the results of improvements, total 71 cases were statistically significant for twelve subjects. Eighty-three percent success of FLMs was achieved against amplification for being an alternative method of amplification in noisy environments. For four subjects, all significant methods gave higher improvements than amplification. As conclusion, specific method recommendations for different noisy environments were done for each subject for getting more speech intelligibility.